2015
DOI: 10.1038/srep10074
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterisation of Unstained and Intact Tissue Micro-architecture by X-ray Computed Micro- and Nano-Tomography

Abstract: Characterisation and quantification of tissue structures is limited by sectioning-induced artefacts and by the difficulties of visualising and segmenting 3D volumes. Here we demonstrate that, even in the absence of X-ray contrast agents, X-ray computed microtomography (microCT) and nanotomography (nanoCT) can circumvent these problems by rapidly resolving compositionally discrete 3D tissue regions (such as the collagen-rich adventitia and elastin-rich lamellae in intact rat arteries) which in turn can be segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 70 publications
1
119
0
Order By: Relevance
“…Lugol's staining has been shown to have no apparent effect on the standard hematoxylin and eosin (HE) tissue staining process [11], but we sought to remove as much as possible from the tissue samples before embedding in order to remove unwanted sources of error during any future 3D histology reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Lugol's staining has been shown to have no apparent effect on the standard hematoxylin and eosin (HE) tissue staining process [11], but we sought to remove as much as possible from the tissue samples before embedding in order to remove unwanted sources of error during any future 3D histology reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Using state-of-the-art laboratory-based mCT systems that are partially coherent due to their small spot size, Walton et al [111] demonstrated that phase enhancement can also be exploited to some extent using commercial mCT scanners. Namely, Walton et al [111] visualized sub-micrometre structures within skin and rat artery walls using mCT and they reported that subsequent histological and immunohistochemical staining was compatible with prior X-ray exposure.…”
Section: Phase-enhanced Imagingmentioning
confidence: 99%
“…Lang et al [4] have been able to identify tumour vasculature and only recently it was reported that phase-contrast imaging in conjunction with phase retrieval at synchrotron facilities enabled simultaneous visualization of blood vessels and nerve fibres in the spinal cord without the need for contrast agents [110]. Using state-of-the-art laboratory-based mCT systems that are partially coherent due to their small spot size, Walton et al [111] demonstrated that phase enhancement can also be exploited to some extent using commercial mCT scanners. Namely, Walton et al [111] visualized sub-micrometre structures within skin and rat artery walls using mCT and they reported that subsequent histological and immunohistochemical staining was compatible with prior X-ray exposure.…”
Section: Phase-enhanced Imagingmentioning
confidence: 99%
“…Crucially though, the volume that can be visualised is usually limited by the opacity of the specimen and the resolution is not equivalent in all three dimensions. In Table 1, we compare optical and electron microscopy 3D visualisation methods according to their achievable resolution, imaging speed, potential to induce artefacts and availability (Weninger et al, 1998;O'Connell et al, 2005;Peddie and Collinson, 2014;Walton et al, 2015). We hope that this table will serve as an initial introduction to some of the more commonly adopted 3D visualisation techniques, but would encourage the interested reader to consult more specialised publications on specific approaches.…”
Section: Optical and Electron Microscopy In Three Dimensionsmentioning
confidence: 99%
“…A handful of studies have attempted to characterise the internal 3D structure of the pressurised vessel wall, but the methods used, such as confocal microscopy, second-harmonic generation imaging and serial blockface electron microscopy, are all limited to the imaging of small tissue volumes and/or limited tissue components (such as fibrillar collagen) (O'Connell et al, 2008;Schrauwen et al, 2012;Schriefl et al, 2013). In our recent study, we therefore aimed to optimise and develop methods for specimen preparation, microCT imaging and image processing that would allow us to visualise, segment and measure the effects of physiological luminal pressure on the major structures of the arterial wall (Walton et al, 2015).…”
Section: Optical and Electron Microscopy In Three Dimensionsmentioning
confidence: 99%